2002
DOI: 10.1099/0022-1317-51-11-941
|View full text |Cite
|
Sign up to set email alerts
|

Different bacteriocin activities of Streptococcus mutans reflect distinct phylogenetic lineages

Abstract: Bacteriocins produced by mutans streptococci are known as mutacins. In this study 16 broadly active mutacin-producing Streptococcus mutans strains from New Zealand, North America and Europe were classified into four groups (A-D) on the basis of differences in their activity in deferred antagonism tests against either the homologous producer strain (to test for presence of self-immunity) or indicator strains Staphylococcus aureus 46 and Enterococcus faecium TE1. Two of the strains included in the study (UA140 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 46 publications
0
42
0
4
Order By: Relevance
“…It should, however, be noted that the collection of strains studied here was in no way structured, and is restricted to examination of regions of the chromosome known or suspected to be dispensable and subject to variation. It is, therefore, not possible to determine how the regions studied may relate to any clonal structure that might be revealed by examination of the phylogenetic relationships between the strains based on data on housekeeping genes in the core genome, as applied by Balakrishnan et al (2002) in their study of mutacins. The dispensable genome may not reflect the true phylogeny of the core genome or population structure of S. mutans, which can better be explored by multilocus sequence typing (Feil, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It should, however, be noted that the collection of strains studied here was in no way structured, and is restricted to examination of regions of the chromosome known or suspected to be dispensable and subject to variation. It is, therefore, not possible to determine how the regions studied may relate to any clonal structure that might be revealed by examination of the phylogenetic relationships between the strains based on data on housekeeping genes in the core genome, as applied by Balakrishnan et al (2002) in their study of mutacins. The dispensable genome may not reflect the true phylogeny of the core genome or population structure of S. mutans, which can better be explored by multilocus sequence typing (Feil, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory spectrum of mutacin N is distinctive compared to that of other mutacins in its ability to inhibit certain S. mutans strains (3,4). The resulting nlmT-deficient mutant, N⌬NlmT, failed to express any inhibitory activity ( Table 2), indicating that the NlmTE ABC transporter is also required for nonlantibiotic mutacin export in S. mutans strain N.…”
Section: Vol 187 2005 Notes 5037mentioning
confidence: 99%
“…Mutacins are peptide or protein antibiotics that are mainly bactericidal for other bacteria of the same or closely related species, as well as for other Gram-positive micro-organisms, and are likely to confer an ecological advantage in diverse bacterial communities such as the dental biofilm (Parrot et al, 1990; Balakrishnan et al, 2002). Some studies have demonstrated that the mutacin activity of S. mutans could be related to the prevalence of this species in the dental biofilm, saliva and dental caries (Berkowitz and Jordan, 1975;Hillman et al, 1987).…”
Section: Introductionmentioning
confidence: 99%